Implementasi Asset Management Berbasis Android PT. PLN ICON PLUS - Pratama, Yogi; Setiowati, Dewi (Universitas Muhammadiyah Riau, 2026)
Digital transformation urges companies to optimize asset management to improve operational efficiency. PT. PLN ICON PLUS, a subsidiary of PT PLN (Persero) specializing in information technology and network infrastructure, still uses manual asset management systems prone to errors and inefficiencies. This study aims to develop an Android-based asset management system integrated with a Laravel backend to enable real-time tracking and asset data updates. The methods used include Fishbone analysis, system design with UML, Android and Laravel-based application development, and black box testing. The implementation results show that the system effectively handles asset loan transactions, category and asset management, and user interactions through an interactive and user-friendly interface. This system improves data accuracy, reduces administrative burden, and facilitates data access for administrators and clients. In conclusion, the developed application successfully replaces manual systems with a more efficient and integrated digital solution.